K-Pop Fan War: Emotional dynamics and psychological impact on Indonesian social media users - Afnilia Ashari Akhmad, Nurul; Ajar Pradika Ananta Tur, Ajar (COMMICAST, 2025)
Fan wars in the K-Pop community illustrate the complex dynamics of online communication among Indonesian social media users. These conflicts, triggered by inter-fandom rivalry, divergent opinions on idols, and provocation across platforms, often escalate into verbal aggression and toxic interactions that harm fan communities. This study analyzes the emotional and psychological impacts of fan wars and identifies aggressive communication patterns through a pragmatic lens. Using descriptive qualitative methods, data were drawn from public interactions on X (formerly Twitter), Instagram, and TikTok, then analyzed with Miles & Huberman’s interactive model. Findings reveal that anonymity encourages verbal aggression and behaviors rarely shown in offline contexts. Three key psychological impacts were identified: stress, trauma, and disengagement. Four dominant forms of aggressive communication emerged: verbal attacks, sarcasm or satire, excessive fanaticism, and provocation. These patterns demonstrate how linguistic strategies in digital discourse directly shape fans’ psychological experiences. This research contributes by connecting pragmatic-linguistic strategies with youth psychological well-being in Indonesia. Beyond description, it offers an understanding of the relationship between language, emotional dynamics, and cultural practices in online fandoms. The findings highlight the urgency of strengthening digital literacy and fostering healthier fandom culture to reduce harmful interactions.